SIMULASI PENGONTROLAN PINTU HALTE BUS WAY MENGGUNAKAN SENSOR LED INFRA RED DAN INTERFACE PORT PARALLEL - Musril, Hari Antoni (IAIN Batusangkar, 2015)
Along with growth of computer technology, at the moment computer not only exploited for the application of having the character of public like reporting processes, data, but also exploited for the operation of equipment and system controller. In this research, writer try the application of personal computer as system of door control at a halte of bus way by using one tide sensor the LED infrared placed in way in at special band of bus way and one tide sensor the LED infrared again placed in constrictor wall. By exploiting electronics component as controller of door of halte of bus way supported with the language programming Borland Delphi 7.0, writer have earned to design a prototype which can give the amenity of management a halte of bus way.Key words: sensor LED infra red, interface port parallel